A PVDF/PVB composite UF membrane improved by F-127-wrapped fullerene for protein waste-water separation. Issue 87 (5th September 2016) - Chen, Gui-E; Zhu, Wei-Wei; Xu, Sun-Jie; Xu, Zhen-Liang; Shen, Qian; Sun, Wei-Guang; Wu, Qiong; Zheng, Xiao-Peng
Abstract : F-127-wrapped fullerene was prepared successfully in a solvent before casting solution preparation, the composite membrane shows excellent hydrophilicity and capacity for protein waste-water separation. Abstract : A novel polyvinylidene fluoride (PVDF)/polyvinyl butyral (PVB) ultrafiltration (UF) membrane was prepared via a non-solvent induced phase inversion (NIPS) method and blended with F-127-wrapped fullerene at different fullerene contents (0.000 wt%, 0.025 wt%, 0.050 wt%, 0.075 wt% and 0.100 wt%, weight of casting solution). The composite membranes were analyzed using SEM, FT-IR, AFM, XPS and TG. The membranes had asymmetrical structures and widened channels, displayed –O–H vibrations at approximately 3700 cm −1, had smooth topographies, and had increased oxygen atom contents and excellent thermal resistances due to the incorporation of additives. The optimal ratios of PVDF, PVB, F-127 and fullerene determined by permeability studies were 16.2 wt%, 1.8 wt%, 1.0 wt% and 0.100 wt%, respectively. Under these ratios, the pure water flux (PWF) was increased, the flux recovery rate (FRR%) was doubled, the reversible fouling ratio ( R r %) was enhanced, and the irreversible fouling ratio ( R ir %) was decreased. Furthermore, dynamic contact angle measurements testified that the surface was more hydrophilic. Besides, mechanical properties, porosity, molecular weight cut-off (MWCO) and pore size distribution were also investigated to evaluate the composite membranes. In protein separation applications, the membranes could provide selectable separation methods for bromelain (33 kDa), ovalbumin (OVA, 45 kDa) and bovine serum albumin (BSA, 68 kDa) up to 98.6%.